2019
DOI: 10.1002/anie.201812356
|View full text |Cite
|
Sign up to set email alerts
|

Making the SF5 Group More Accessible: A Gas‐Reagent‐Free Approach to Aryl Tetrafluoro‐λ6‐sulfanyl Chlorides

Abstract: Modern pentafluorosulfanyl (SF5) chemistry has an Achilles heel: synthetic accessibility. Herein, we present the first approach to aryl‐SF4Cl compounds (key intermediates in state‐of‐the‐art aryl‐SF5 synthesis) that overcomes the reliance on hazardous fluorinating reagents and/or gas reagents (e.g. Cl2) by employing easy‐to‐handle trichloroisocyanuric acid, potassium fluoride, and catalytic amounts of acid. These simple, mild conditions allow direct access to aryl‐SF4Cl intermediates that either have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
92
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 31 publications
3
92
1
8
Order By: Relevance
“…These features predict great potential for this functional group in chemistry . However, the accessibility of SF 5 compounds is still rather difficult even though a mild synthesis starting from disulfides has been established by Umemoto and co‐workers in 2012 and further facilitated by Pitts, Togni, and co‐workers quite recently . However, formation of the C−S bond still requires the use of extraordinarily toxic reagents, like S 2 F 10 , and the mixed‐sulfur halogenides SF 5 Cl and SF 5 Br.…”
Section: Figurementioning
confidence: 99%
“…These features predict great potential for this functional group in chemistry . However, the accessibility of SF 5 compounds is still rather difficult even though a mild synthesis starting from disulfides has been established by Umemoto and co‐workers in 2012 and further facilitated by Pitts, Togni, and co‐workers quite recently . However, formation of the C−S bond still requires the use of extraordinarily toxic reagents, like S 2 F 10 , and the mixed‐sulfur halogenides SF 5 Cl and SF 5 Br.…”
Section: Figurementioning
confidence: 99%
“…Following the chalcogen series, the reactivity of diaryl disulfides, diaryl diselenides, and diaryl ditellurides under TCICA/KF conditions has been studied in our laboratory, as well as the behavior of aryl(trifluoromethyl)tellanes (Figure ) . Conversely, the reactivity of aryl(trifluoromethyl)sulfanes and selanes under similar conditions has yet to be explored .…”
Section: Figurementioning
confidence: 99%
“…Adapted from the conditions used for oxidative fluorination of diaryl disulfides, we began screening with phenyl(trifluoromethyl)sulfane using 9.0 equiv TCICA, 16 equiv KF, and 10 mol % TFA in MeCN at room temperature overnight. Under these conditions, we found that the substrate is converted to difluoro(phenyl)(trifluoromethyl)‐λ 4 ‐sulfane ( 1 ) in 81 % yield by 19 F NMR analysis.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[6] Jedoch ist der Zugang von SF 5 -Verbindungen immer noch ziemlich schwierig, obwohl eine milde Synthese ausgehend von Disulfiden durch Umemoto im Jahr 2012 etabliert wurde [7] und kürzlich durch Pitts und Togni weiter vereinfacht wurde. [8] Der Aufbau der C-S-Bindung erfordert jedoch immer noch extrem toxische Reagenzien, wie S 2 F 10 , und die gemischten Schwefelhalogenide SF 5 Cl und SF 5 Br.…”
unclassified